Interlayer gap widened α-phase molybdenum trioxide as high-rate anodes for dual-ion-intercalation energy storage devices - Yu, Minghao; Shao, Hui; Wang, Gang; Yang, Fan; Liang, Chaolun; Rozier, Patrick; Wang, Cai-Zhuang; Lu, Xihong; Simon, Patrice; Feng, Xinliang (Nature communications, 2020)
Employing high-rate ion-intercalation electrodes represents a feasible way to mitigate the inherent trade-off between energy density and power density for electrochemical energy storage devices, but efficient approaches to boost the charge-storage kinetics of electrodes are still needed. Here, we demonstrate a water-incorporation strategy to expand the interlayer gap of α-MoO 3 , in which water molecules take the place of lattice oxygen of α-MoO 3 . Accordingly, the modified α-MoO 3 electrode exhibits theoretical-value-close specific capacity (963 C g −1 at 0.1 mV s −1 ), greatly improved rate capability (from 4.4% to 40.2% at 100 mV s −1 ) and boosted cycling stability (from 21 to 71% over 600 cycles). A fast-kinetics dual-ion-intercalation energy storage device is further assembled by combining the modified α-MoO 3 anode with an anion-intercalation graphite cathode, operating well over a wide discharge rate range. Our study sheds light on a promising design strategy of layered materials for high-kinetics charge storage. The power/energy trade-off is a common feature seen in a Ragone plot for an electrochemical storage device. Here the authors approach this issue by showing water-incorporated α-MoO 3 anodes with expanded interlayer gaps, which allow for the assembling of dual-ion energy storage devices.